Effects of Steps to Success Exercise Program in Weight Management For Psychiatric Patients Taking Atypical Antipsychotic Drugs - Estoque, Homelo V. (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Patients taking atypical antipsychotics are in danger of antipsychotic-induced weight gain. Weight increases rapidly in the initial period after starting antipsychotics. Cardiovascular and cerebrovascular morbidity and mortality and reduced quality of. Both nonpharmacologic prevention and intervention strategies have shown modest effects on weight. Changes in physical appearance can lead to body image issues and problems with self-esteem, which in turn could lead to poor compliance with medication. Purpose: This study aimed to evaluate the effectiveness of an exercise program that can benefit patients who are gaining weight related to atypical antipsychotic agent intake.Methods: A quasi-experimental research design was undertaken. The research setting was held in a general tertiary medical teaching/training medical facility owned by the Philippine government. There are 31 respondents for this study 12 were males and 19 were females who were chosen from the list of the in-patients utilizing the universal sampling technique. Data were gathered using a self-formulated tool to collect mostly demographic data which is adopted from the National Alliance for Mental Health.Results: Patients’ diagnosis tends to have a positive relationship with weight loss. Respondents diagnosed with bipolar with psychotic features showed to have loss weight more than the diagnosed with schizophrenia. The results of this study showed that patient’s adhering to the exercise program had lost weight after the course. Conclusion: Activity and exercise are especially important for people living with mental illness. Furthermore, physical activity does not only help patients manage their weight but to serve as diversional activity that adds vitality for patients in the facility